Occurrence of hepatotoxicity with pazopanib and other anti-VEGF treatments for renal cell carcinoma: an observational study utilizing a distributed database network. - Shantakumar, Sumitra; Nordstrom, Beth; Djousse, Luc; Hall, Susan; Gagnon, David; Fraeman, Kathy; Herk-Sukel, Myrthe; Chagin, Karen; Nelson, Jeanenne; Nordstrom, Beth L; Hall, Susan A; Gagnon, David R; et al. (Cancer Chemotherapy & Pharmacology, 2016)
Purpose: To quantify the hepatic safety of pazopanib and comparator anti-vascular endothelial growth factor (VEGF) therapies in clinical practice among renal cell carcinoma (RCC) patients.Methods: A population-based cohort study of new anti-VEGF users was conducted in two US healthcare databases, Department of Veterans Affairs (VA) and an oncology practice network (Altos), and the PHARMO Database Network in The Netherlands. A common protocol was used to collect liver chemistry (LC) data from anti-VEGF initiation through 4 years of follow-up. In the VA population, suspected drug-induced liver injury (DILI) outcomes were investigated via chart review, with adjudication by hepatologists.Results: In Altos and VA, respectively, the total RCC patients were: pazopanib (156, 243), bevacizumab (122, 99), sorafenib (82, 249) and sunitinib (285, 751). PHARMO contained too few patients to be included. Few cases of alanine aminotransferase (ALT) ≥8× the upper limit of normal were seen across the anti-VEGF cohorts; incidence rates (per 100 person-years) ranged from 0 (sunitinib) to 8.2 (pazopanib) in Altos and from 0 (bevacizumab and sorafenib) to 2.1 (pazopanib) among VA patients. No cases of Hy's law identified by combination LC elevations were seen in patients treated with pazopanib or bevacizumab; one case was observed in those treated with sorafenib, and two cases were found among sunitinib users. One case of adjudicated DILI was observed in a sunitinib-treated patient; none were found among patients treated with pazopanib, bevacizumab or sorafenib.Conclusions: Severe liver injury occurred infrequently during exposure to pazopanib and other anti-VEGF therapies in a population-based setting.